Judicial opportunities and the death of SHAC: legal repression along a cycle of contention. (2nd September 2016) - Ellefsen, Rune
Abstract: Focusing on the British animal rights campaign against Huntingdon Life Sciences, this article investigates how changing judicial opportunities effectively cause the demobilization of a social movement campaign, explaining the central role of law and criminal justice in movement repression. The study identifies four forms of legal repression arising in response to the UK organization Stop Huntingdon Animal Cruelty: elite-initiated protest control, targeted criminalization, leadership decapitation and extended incapacitation. The analysis demonstrates the need to widen repression research beyond the policing of protest events, to cover how social movement activists are controlled after arrest. It concludes by arguing for the inclusion of a stage-dimension in repression research to better grasp the crucial role of private elites in the initiation of repression. The study builds on qualitative data from Britain, obtained by participant observation, trial observation and interviews, covering both protestors and their adversaries.